2010
DOI: 10.1098/rsif.2010.0548
|View full text |Cite
|
Sign up to set email alerts
|

The pathway to intelligent implants: osteoblast response to nano silicon-doped hydroxyapatite patterning

Abstract: Bioactive hydroxyapatite (HA) with addition of silicon (Si) in the crystal structure (silicondoped hydroxyapatite (SiHA)) has become a highly attractive alternative to conventional HA in bone replacement owing to the significant improvement in the in vivo bioactivity and osteoconductivity. Nanometre-scaled SiHA (nanoSiHA), which closely resembles the size of bone mineral, has been synthesized in this study. Thus, the silicon addition provides an extra chemical cue to stimulate and enhance bone formation for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
(41 reference statements)
2
35
0
Order By: Relevance
“…These NPs potentially have an important role in bone tissue engineering, forming nanosized building blocks for bone tissue repair and/or replacement. Thian et al evaluated the bioactivity of electrohydrodynamic atomized nanoapatite [9], as well as studying nanostructured HA coatings produced using magnetron sputtering and electrohydrodynamic spraying [10][11][12][13]. Nanoapatite has also been observed to form in various shapes, and with different aspect ratios, when synthetic HA has been incubated in simulated body fluid that contains similar ion levels to blood plasma [14].…”
Section: Introductionmentioning
confidence: 99%
“…These NPs potentially have an important role in bone tissue engineering, forming nanosized building blocks for bone tissue repair and/or replacement. Thian et al evaluated the bioactivity of electrohydrodynamic atomized nanoapatite [9], as well as studying nanostructured HA coatings produced using magnetron sputtering and electrohydrodynamic spraying [10][11][12][13]. Nanoapatite has also been observed to form in various shapes, and with different aspect ratios, when synthetic HA has been incubated in simulated body fluid that contains similar ion levels to blood plasma [14].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 With a thickness of 10-20 nm and HA crystals with similar size and shape as those found in human bone, it was suggested that the novel coating facilitates implant integration. 27,29,30 Furthermore, since the nanosized HA coating is a monolayer, the risk of detachment is hypothesized to be lower than that of the thicker HA coatings. A recently published study, using an identical HA coating as in the present study, revealed a higher mean bone-to-implant contact for HA, indicating a higher level of osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the concept of a nano-sized silicon-substitute hydroxyapatite (nanoSiHA) coated implant with 3-D surface topographies to guide bone tissue remodelling, has become attractive. Recently, a new technique, template-assisted electrohydrodynamic atomization (TAEA) spraying, is of considerable interest in surface topography formation [6,7]. TAEA has been developed from electrohydrodynamic atomization spraying, an electric-driven jet-based deposition method.…”
Section: Introductionmentioning
confidence: 99%